Determination of Milk Products in Ceramic Vessels of Corded Ware Culture from a Late Eneolithic Burial - Lukáš Kučera; Jaroslav Peška; Pavel Fojtík; Petr Barták; Diana Sokolovská; Jaroslav Pavelka; Veronika Komárková; Jaromír Beneš; Lenka Polcerová; Miroslav Králík; Petr Bednář (Molecules, 2018)
In this study, a soil from two ceramic vessels belonging to Corded Ware culture, 2707⁻2571 B.C., found in a cremation grave discovered in Central Moravia, Czech Republic, was analyzed using matrix-assisted laser desorption/ionization⁻mass spectrometry (MALDI⁻MS) combined with advanced statistical treatment (principal component analysis, PCA, and orthogonal projection to latent structures discriminant analysis, OPLS-DA) and by enzyme-linked immunosorbent assay (ELISA). MALDI⁻MS revealed the presence of triacylglycerols in both vessels. This analytical technique was used for the analysis of the soil content from archaeological ceramic vessels for the first time. Targeted ELISA experiments consequently proved the presence of milk proteins in both ceramic vessels. These results represent the first direct evidence of the use of milk or dairy products in the Eneolithic period in Moravian Corded Ware Culture and help to better understand the diet habits and living conditions of Eneolithic populations in Central Europe.